2009
DOI: 10.1111/j.1095-8312.2009.01302.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of an ancient Hepatozoon species parasitizing the ‘living fossil’ marsupial ‘Monito del Monte’ Dromiciops gliroides from Chile

Abstract: The Microbiotheriid Dromiciops gliroides, also known as 'Monito del Monte', is considered to be a threatened species and the only living representative of this group of South American marsupials. During the last few years, several blood samples from specimens of 'Monito del Monte' captured at Chiloé island in Chile have been investigated for blood parasites. Inspection of blood smears detected a Hepatozoon species infecting red blood cells. The sequences of DNA fragments corresponding to small subunit ribosoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 30 publications
3
27
0
2
Order By: Relevance
“…También se registró un parásito digestivo, el nemátodo Pterygodermatites sp. (Rictulariidae) y la presencia de un nuevo hemoparásito, una especie ancestral dentro del grupo Hepatozoon sp., que habría evolucionado en conjunto con Dromiciops (Merino et al 2009). Su potencial vector específico, en base a evidencia genética, sería la garrapata Ixodes neuquenensis (Merino et al 2009).…”
Section: Demografía Y Conservación Del Monito Del Monte (Dromiciops Gunclassified
“…También se registró un parásito digestivo, el nemátodo Pterygodermatites sp. (Rictulariidae) y la presencia de un nuevo hemoparásito, una especie ancestral dentro del grupo Hepatozoon sp., que habría evolucionado en conjunto con Dromiciops (Merino et al 2009). Su potencial vector específico, en base a evidencia genética, sería la garrapata Ixodes neuquenensis (Merino et al 2009).…”
Section: Demografía Y Conservación Del Monito Del Monte (Dromiciops Gunclassified
“…The majority of descriptions given in previous literature have actually been based mainly on gametocyte morphology without considering the life cycle, and as a result most of the species were superficially referred to as members of the genus Haemogregarina (Saoud et al 1996, Sloboda et al 2007. Recently, however, many studies have indicated that integration of morphological and phylogenetic approaches to the identification of the haemoprotozoan parasites and epidemiological investigation this parasitosis is more effective than the traditional examination of blood smears (Merino et al 2009, Vilcins et al 2009. Also, molecular data is of particular value for the systematic of haemoprotozoan (Barta et al 2012), considering both the very similar morphological characteristics of most species and the low host specificity.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, molecular methods have been increasingly used for the detection of protists in both wild and domestic animals. Compared to more traditional approaches, such as microscopy, molecular methods benefit from good specificity and sensitivity in detecting parasitic infections (e.g., Rubini et al 2005, Merino et al 2009), especially at low parasitemia levels (Moody 2002), they are straightforward and are relatively low cost and not time consuming, thus allowing the screening of large numbers of samples in a reproducible manner. Moreover, molecular data provides additional and valuable information on the diversity of parasitic organisms and their genetic relationships.…”
Section: Introductionmentioning
confidence: 99%